New data about consistency of skin prick-tests results with specific immunoglobulin E level and food allergy symptoms in children of opisthorchiasis endemic areas - L. M. Ogorodova; O. S. Fyodorova; I. A. Deyev (Бюллетень сибирской медицины, 2010)
Aim: to investigate the consistency of skin prick-tests results with specific IgE level and symptoms of food allergy. The criteria of food allergy in children of opisthorchiasis endemic areas were developed: symptoms of food allergy within 2 hours, skin pricktests weal size ≥1 mm and (or) specific IgE ≥0,35 kUA/l.